Restoration of knee functions in football players after injuries - Makarova E.V. ,; Egorov D.E. ,; Kupreenko M.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to develop and test the effectiveness of individual physical rehabilitation programs for football players with knee injuries. Methods and structure of the study. Fifteen football players were monitored from 2022 to 2024 at the City Polyclinic No. 1 in Melitopol, based on the medical and physical culture dispensary. As part of the monitoring, the results of ultrasound examinations were analyzed, the Oxford knee assessment scale was used, as well as a special knee joint assessment scale. Based on the initial examination of the athletes and taking into account their clinical condition and functional capabilities, personalized recovery programs were developed for each of them. These programs included a set of therapeutic physical exercises, physiotherapy procedures and a course of massage. Results and conclusions. Physical rehabilitation was carried out in three consecutive phases: initial, functional and final. During these phases, specific tasks were solved, starting with preventing knee joint stiffness, strengthening the muscular system of the limb and ending with complete restoration of the neuromuscular system and return to sports activities. The success of the implemented measures was confirmed by the improvement of the observed parameters.